International Marketing - Romi Alhadid Rangkuti; Nuri Aslami (Indonesian Journal of Multidisciplinary Science, 2022)
International marketing is the performance of business activities designed to plan, price, promote and direct the flow of a company's goods and services to consumers or users in more than one country for profit. The purpose of this study is to reveal the meaning of International Marketing, to explain the background of the emergence of International Marketing, to explain the various objectives of International Marketing, to explain in general the related and influencing factors, and to explain in general the steps in International Marketing. This study uses a qualitative approach with descriptive analysis method, this method is considered relevant and in accordance with the research to be carried out, namely to obtain a true understanding of International Business in Indonesia. International business is unavoidable because in fact there is not a single country in the world that can meet all the needs of its country from goods or products produced by the country itself.